Analysis of Factors Influencing the Absorption of the 2017-2021 Dompu District Government Expenditure Budget - Nur Nabillah Putri Suciati; Hadi Mahmudi; Eka Agustiani (Experimental Student Experiences, 2024)
The purpose of this study was to determine the effect of budget planning, budget execution and human resources on the absorption of the budget in the Government of Dompu District. The type of research used is descriptive quantitative research with questionnaire data collection techniques. The population of this study were all SKPDs in Dompu Regency and the samples used were the BAPPEDA and LITBANG of Dompu Regency, the BPKAD of Dompu Regency and the Secretary of the DPRD of Dompu Regency. The test conducted in this study is multiple linear regression analysis. The results of the study show that both partially and simultaneously the variables of budget planning, budget execution and human resources have a significant effect on the absorption of the Dompu Regency budget.